The Constitutionality of Forest Protection in the Era of Decentralization: A Juridical Analysis of the Weaknesses in Anti-Illegal Logging Enforcement - Amirullah Amirullah; Sri Rahayu; Jenny Ermalinda; Mardiana Hasbullah (Journal of Innovative and Creativity, 2025)
This study analyzes the constitutionality of Indonesia’s forest protection within the decentralization regime by combining normative and empirical approaches. Article 28H paragraph (1) of the 1945 Constitution guarantees every person the right to a good and healthy environment; however, data from 2019-2025 reveal a significant gap between constitutional norms and practice: 2,133 cases of illegal logging in Sulawesi, 22,000 hectares of forest fires in Riau, Sonokeling logging in TTU valued at IDR 600 million, and the smuggling of 55 containers of illegal timber through sea routes. The study finds that fragmented authority due to decentralization, weak inter-agency coordination, and limited enforcement capacity have created an enforcement gap that results in violations of citizens’ constitutional rights. Using the frameworks of environmental constitutionalism, multi-level governance, and the rule of law, this research argues that the state’s failure to fulfill its obligations in forest management under Articles 28H and 33 of the 1945 Constitution constitutes a denial of the public trust doctrine. The main recommendations include establishing a “Green Constitutional Authority,” creating cross-provincial task forces, harmonizing central–regional regulations, and implementing a model of constitutional-based forest governance to ensure forest protection as a constitutional commons that is ecologically just and sustainable.